Formation of the Integrated Approach to the Assessment of the Socio-Economic Development of Regions - Valentina Vasilievna Kislitsyna; Larisa Sergeevna Cheglakova; Vasily Mikhaylovich Karaulov; Anna Nikolaevna Chikisheva (Экономика региона, 2017)
The integrated approach to the assessment of the socio-economic development of subjects of the Russian Federation, which is characterized by systematic character and novelty, is presented in the article. This approach is based on the modern techniques used in this sphere. The main purpose of the comprehensive assessment of a region’s socio-economic development level is the elaboration of a possible solution for the strategic development issues taking into account spatial, geographical, natural, socioinstitutional and other features. The authors propose to estimate the socio-economic climate of the subjects of the Russian Federation by the average values of socio-economic indexes for the three-year period. For comparability of multitemporal indicators and regional distinctions, the indicators measured in monetary units are transformed in the form of their relation to the cost of the fixed set of consumer goods and services. In addition, we estimate the dynamics of comparable indicators in absolute and relative expression and introduce scales for the assessment of the dynamics of socio-economic situation and a level of quality (stability) of dynamics. On the basis of this technique, the authors examine the socio-economic situation of territorial subjects of the Russian Federation in 2012–2014. As a result, we have revealed one of the problems of socio-economic development — the imbalance of the dynamics of the main socio-economic indexes. In the studied period, 7 regions have shown moderate or high growth of the integrated indicator (not less than 9 %), but in 4 of them, the growth was unbalanced of poor quality. Moreover, further 11 regions have shown a considerable and unbalanced decrease in the social-economic situation. This has been revealed on the basis of the integrated indicator. Thus, the offered approach can be applied for an assessment of the level of socio-economic development in Russian regions in medium-term prospect. It can be used for the development of the basic methodological statements as well as for the identification of cause-effect relationship and justification of the priority directions for the development of the subjects of the Russian Federation.